Emerging Digital Micromirror Device Based Systems and Applications V 2013
DOI: 10.1117/12.2003601
|View full text |Cite
|
Sign up to set email alerts
|

Binary pattern codification strategies in an active stereoscopic system based on flexible image guides

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In the scope of the time multiplexing methods, phase-shift and gray code methods are two possibilities. Our study in [13] showed that the best reconstruction results were obtained with phase shift algorithms, however these algorithms need phase unwrapping and high number of patterns was needed to optimize the axial resolution. Gray code is well suited for lower resolution results, but with fewer projected patterns.…”
Section: Structure Of Compact Optical Probementioning
confidence: 93%
See 1 more Smart Citation
“…In the scope of the time multiplexing methods, phase-shift and gray code methods are two possibilities. Our study in [13] showed that the best reconstruction results were obtained with phase shift algorithms, however these algorithms need phase unwrapping and high number of patterns was needed to optimize the axial resolution. Gray code is well suited for lower resolution results, but with fewer projected patterns.…”
Section: Structure Of Compact Optical Probementioning
confidence: 93%
“…In order to design a compact system, flexible image guides have been integrated in a compact optical probe. This probe is an improved model of the one presented in [13] and its size is fitted for colonoscopy. The view angle switch is achieved with two miniature digital electromagnetic actuators on witch mobile mirrors are mounted.…”
Section: Introductionmentioning
confidence: 99%
“…It is connected to a miniaturized optical probe composed of a diaphragm and objective lenses as presented in [12]. The pattern coming from the image guide 1 enters into the optical probe and is projected onto the object surface.…”
Section: System Structure Descriptionmentioning
confidence: 99%
“…By shifting the image guide through the focusing stages, an optical conjugation between the object to be measured and the ends of the image guides can be obtained. More details regarding this procedure is provided in [12]. The active part of the measuring system consists of three parts as shown as in Fig.5(b).…”
Section: Experimental Realizationmentioning
confidence: 99%
See 1 more Smart Citation